2008
DOI: 10.1295/polymj.pj2008165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligo(oxyethylene) Methacrylate-ended Poly(n-hexyl isocyanate) Rodlike Macromonomers and Their Radical Copolymerization Behavior with Methyl Methacrylate

Abstract: A series of novel poly(n-hexyl isocyanate) (PHIC) rodlike macromonomers having an -methacryloyloxyoligo(oxyethylene) group and an !-acetyl group (MA-EO m -HIC-n-Ac, where m and n are the degrees of polymerization of oxyethylene (EO) and HIC, respectively) have been prepared. They were prepared by living coordination polymerization of HIC using corresponding titanium(IV) alkoxide complexes as an initiator in CH 2 Cl 2 at room temperature, followed by termination with acetic anhydride as a terminator in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In previous papers, we reported the synthesis and characterization of rod-like styryl-ended or α-methacryloyl-ω-acetyl ended poly­( n -hexyl isocyanate) (PHIC) macromonomers (VB-HIC- N s or MA-HIC- N s , where N s is the weight-averaged degree of polymerization of HIC), their radical copolymerizabilities, , and conformational properties of the resulting rod brushes. ,, The value of λ M –1 of the rod brushes linearly increased with the increasing of N s that followed the scaling law of λ M –1 ∝ N s 1 . The observed power law exponent value could not be explained by the theories for the rod brushes …”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we reported the synthesis and characterization of rod-like styryl-ended or α-methacryloyl-ω-acetyl ended poly­( n -hexyl isocyanate) (PHIC) macromonomers (VB-HIC- N s or MA-HIC- N s , where N s is the weight-averaged degree of polymerization of HIC), their radical copolymerizabilities, , and conformational properties of the resulting rod brushes. ,, The value of λ M –1 of the rod brushes linearly increased with the increasing of N s that followed the scaling law of λ M –1 ∝ N s 1 . The observed power law exponent value could not be explained by the theories for the rod brushes …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atoms of the methylene groups of PHIC were as follow: (d, e, f, 1.263–1.326 ppm), (g, 1.445–1.521ppm), (h, 3.615–3.682 ppm). 19,20,23,24,30 The end of the chain (i) gives a weak peak at 7.074 ppm. 30,35,44 Number-average molecular weight (normalM¯normaln) and the number of units in each block of the copolymer were calculated from the 1 H NMR spectrum by the following equation 45 :Where I a , I c , and I i are the integrals of a, c, and i signals in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, poly (n-hexyl isocyanate) (PHIC) and its copolymers have attracted considerable attention because of their potential applications and unique properties in areas such as chiral recognitions, optical switches, liquid crystals, degradable materials, nanocomposites, blend of polymers, electrical devices, biomaterials, nanowires, thermoreversible gels, and activators. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] These copolymers are so important that various behaviors of linear and nonlinear block copolymers based on PHIC have been investigated by Vazaios et al 32 The known methods used for copolymerization of PHIC are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the preparation and characterization of the macromonomer have been described in previous papers. [31][32][33] Briefly, the initiator, HEMACpTiCl 2 , was synthesized as follows. In a dry box, a solution of HEMA (4.56 mmol) in 5 ml of dry THF was slowly added to a solution of trichlorocyclopentadienyl titanium (4.56 mmol) in 5 ml of dry THF in a 50 ml three-necked flask with a magnetic stir bar and a tube containing dry triethylamine to trap the produced HCl.…”
Section: Preparation Of Phic Macromonomer (Ma-hic-61-ac)mentioning
confidence: 99%